2011
DOI: 10.1007/s10384-011-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timing of initial surgery for infantile esotropia on the severity of dissociated vertical deviation

Abstract: Early surgery for infantile esotropia decreases the severity of DVD and lowers the need for an additional operation for DVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…It is reported that, in infantile esotropia, DVD can be decreased by early surgery [27]. All of the subjects in the current study were adult cases with abnormal binocular vision development caused by strabismus; however, we were unable to determine the sequential retinal morphology.…”
Section: Is There a Relationship Between Dvd And Gcc Thickness?mentioning
confidence: 72%
“…It is reported that, in infantile esotropia, DVD can be decreased by early surgery [27]. All of the subjects in the current study were adult cases with abnormal binocular vision development caused by strabismus; however, we were unable to determine the sequential retinal morphology.…”
Section: Is There a Relationship Between Dvd And Gcc Thickness?mentioning
confidence: 72%
“…This was supported by a study in a Japanese population. 17 However they came up with an interesting observation that early surgery is associated with less severe i.e. latent rather than manifest DVD, which indicates that a surgery for DVD could be avoided.…”
Section: Infantile Esotropiamentioning
confidence: 99%
“…[15][16][17][18] DVD'nin binoküler fonksiyona etkisi ve ambliyopiye yol açabilmesi sebebiyle tanınması, takibi ve gerekirse tedavisi önemlidir. DVD'lerde tedavinin amacı, hastanın füzyonel mekanizmalarını genişletmektir.…”
Section: Gereç Ve Yöntemlerunclassified